The Association between The Thickness of the Endometrium at the Day of Human Chorionic Gonadotrophin Injection and the Outcome Intracytoplasmic Sperm Injection - Zainab Alkhafajy1 , Zainab Abd alkathem fatnan2 , Hayfaa Dinar Jaber AL Habeeb3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Clinically during ICSI, controlled ovarian stimulation (COS) is a famous way to increasethe number of mature oocytes picked up. This method must be asseeed with a substantial danger of ovarianhyper stimulation syndrome (OHSS), which occurred if follicular induction is very strong. Along withmultifollicular growth, COS is also resulting in increased serum concentration of estradiol (E2) that inturn may has effect on the receptivity of the endometrium .The high serum E2 concentration through COSmay resulting either with an increased chance of pregnancy or an impaired reproductive score secondary tochange in endometrial receptivity. Aim of the study: to assess the impact of thickness of the endometriumat the day of hCG administration on the winning of intracytoplasmic sperm injection (ICSI) cycles. Patientsand method: A retrospective study in which 235 women who were undergo one time of ICSI cycle wereevaluated in this retrospective study, All patients were treated with gonadotrophin agonist either short orlong protocol. The patients were according to endometrial thickness they were categorized into three groupsI (<7mm), II (7-14mm), and group III (>14mm). Results: the rate of clinical pregnancy was increased ingroup II (7-14mm) than other two groups depending on endometrial thickness measurement.Conclusion: endometrial thickness 7-14mm is associated with higher rate of clinical pregnancy